Analisis Pentingnya Growth Mindset bagi Anak Sekolah yang Beragama Kristen Kelas IX SMP Negeri 1 Bakti Raja Tahun Pembelajaran 2023/2024 - Risma Nainggolan; Senida Harefa; Nurelni Limbong; Elvri T. Simbolon; Frainskoy Rio Naibaho (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to analyze the importance of a growth mindset in Christian religious education as an effort to improve the quality of student learning. This research was conducted using descriptive qualitative research methods. Data was obtained through observation, interviews and documentation. Data analysis was carried out using several stages such as data collection, data reduction, data presentation and drawing conclusions. The research results show that education has an important role in developing children's intelligence, mindset and personality. Christian religious education teachers have the responsibility to develop students' mindsets through implementing a Growth Mindset and appropriate teaching strategies. This research concludes that developing a Growth Mindset can help students achieve better academic success and personal development. By having a growth mindset, students see challenges as opportunities to learn and develop and do not respond to them as obstacles. By having a growth mindset, students also have more self-confidence. Based on the research results, it is recommended that Christian religious education teachers continue to strengthen the application of the Growth Mindset in their teaching. In addition, further research can be conducted to observe the effectiveness of the teaching strategies used in developing a Growth Mindset in students.